System, Expression, and Timbre: Expanding the Taxonomy of Counterpoint in Contemporary Choral Music - Farlina, Nina; Hermansyah, Kusen Dony (Indonesian Scientific Publication, 2025)
This study explores the redefinition of counterpoint in 21st-century choral music, focusing on its systemic and re-contextualized modalities across seven representative works. The research investigates how composers such as David Lang, Arvo Pärt, Caroline Shaw, Eric Whitacre, and Tarik O’Regan reinterpret contrapuntal strategies in light of contemporary aesthetic and structural demands. Using a multi-dimensional analytical framework, the study evaluates contrapuntal types (e.g., imitation, canon, tintinnabuli), polyphonic density, and timbral techniques through segment-based coding. Quantitative tools such as the Voice Overlap Index (VOI) and Polyphonic Density Index (PDI) supplement traditional score analysis, enabling cross-style comparison. Inter-rater reliability measures and algorithmic analyses ensure rigor and reproducibility. Findings reveal that systemic counterpoint evident in Lang's process layering and Pärt’s algorithmic tintinnabuli functions as a generative architecture rooted in structural clarity. Conversely, re-contextualized counterpoint employed by Shaw, Whitacre, and O’Regan blends text-driven imitation, modal interplay, and timbral diversity for expressive depth. The emergence of “timbral counterpoint” underscores the increasing role of extended vocal techniques in contrapuntal design. The article concludes that counterpoint in contemporary choral music is both a structural and expressive tool, redefined to accommodate modern compositional priorities. By establishing a typology that includes systemic, expressive, and timbral counterpoint, this study expands the analytical vocabulary available to scholars and practitioners.